Stability analysis of roadheaders with mini-disc. (September 2017) - Acaroglu, O.; Erdogan, C.
Abstract: Roadheaders, one of the mechanized excavation equipment, has an exceptional place among those other excavation machines. However they are not suitable for using in hard and abrasive rock conditions since their cutting tools wear out rapidly. Therefore new technologies have been developed and one of them is mini-disc cutter technology. There are some experimental studies made to carry out efficiency of using these cutters in roadheaders. Determination of the stability states of roadheaders is also important matter for the efficiency of the excavation. For this reason, new machine designs should be analyzed considering stability states. There is an analysis method to estimate numeric values of both longitudinal and transverse cutting head type roadheaders by establishing stability equations for the states of turning around the vertical axis, turning to the side direction, turning to the back direction and sliding in all cutting modes. In this study, stability of roadheaders with mini disc cutters have been analyzed and discussed in different cutting modes and compared with roadheaders equipped classic point attack cutters.